Social Justice Narrative Inquiry: A Queer Crit Perspective - Mitsunori Misawa (Adult Education Research Conference, 2012)
Social justice narrative inquiry is an important research methodology in social justice research, especially for when examining the intersectionality of race and sexual orientation. This paper intends to: 1) conceptualize how social justice narrative inquiry contributes to knowledge production in the field of adult education in terms of positionality and its influence on the web of power dynamics; 2) theorize social justice narrative inquiries for social justice education and social justice research; and 3) demonstrate how a queer crit perspective (a queer perspective under Critical Race Theory) can be used in social justice narrative inquiry. Keywords: social justice narrative inquiry, queer crit, intersectionality, racism, homophobia.
Keywords: social justice narrative inquiry; queer crit; intersectionality; racism; homophobia